Factors influencing the implementation of best practice in burn care in Western Australia. Issue 5 (August 2021) - McWilliams, T.L.; Twigg, D.; Hendricks, J.; Wood, F.
Highlights: The main supporting factor for burn care in Western Australia was identified as the telehealth service IT issues were identified as providing challenges to clinicians. Multiple factors influence burn care and models of care which acknowledge these factors can help facilitate optimal patient care. Abstract: Aims and objectives: The study aimed to determine the factors which influence clinician behaviour and adherence to best practice when clinicians provide the initial care for paediatric burn patients admitted to a burns unit. Background: Optimal initial care of burn patients influences morbidity and mortality. Non-burn specialist clinician adherence to best practice is influenced by previously unexplored factors. Design: General inductive qualitative methods were used to explore factors which influenced clinicians providing acute pre-admission burn care for children in Western Australia. Methods: Interviews of nineteen clinicians using standardised open-ended questions based on the Gilbert Behaviour Engineering Model were used to collect data. Results: The main influencing factors identified were the telehealth service which supported practice, whilst IT issues provided challenges to clinicians. Conclusion: Telehealth services support clinicians when providing burn care, however IT issues are an major barrier to both best practice and accessing the telehealth service and should be optimised to support clinical care Impact statement: What does this paper contribute to the wider global community? It provides burn clinicians with an insight into the factors which facilitate optimal care for patients prior to transfer to burn units, as well as the barriers faced by non-burn specialist clinicians when patients initially present for care. Models of care which acknowledge these factors can help facilitate optimal patient care.